Delamination detection in CFRP panels using EMI method with temperature compensation. (1st September 2016) - Wandowski, T.; Malinowski, P.H.; Ostachowicz, W.M.
Abstract: In this paper result of detection and localization of artificially initiated delaminations in carbon fiber reinforced polymer (CFRP) samples were presented. Damage detection was based on electromechanical impedance method (EMI). This method utilizes electromechanical coupling of piezoelectric transducer with host structure. Due to this coupling mechanical resonances of structure can be seen in electrical impedance characteristic of a piezoelectric transducer. In the research real part of electrical impedance (resistance) was measured. Delamination in CFRP sample caused frequency shift of certain resonance frequencies visible in resistance characteristic. In this paper also changing temperature effects on EMI method were investigated. In order to remove this temperature induced effects compensation algorithm based on signal cross-correlation was utilized.